THEORETICAL AND METHODOLOGICAL PRINCIPLES OF INVESTMENTS AND THEIR EFFECTIVE USE IN BUSINESS ACTIVITY (Marketing Journal, 2025)
The article analyzes the role of investments in the economy and their importance in the development of entrepreneurial activity. It examines the theoretical foundations of investment, mechanisms for attracting capital, and methodological approaches to the effective use of investments by business entities. Special attention is paid to the stability of the investment environment, the efficiency of capital investments, and risk management principles. Based on the research results, scientific recommendations ar e proposed to enhance investment activity, strengthen the impact of investments on economic growth, and improve investment policy. 518
Keywords: investment; investment environment; capital investment; entrepreneurship; efficiency; risk management; investment policy; economic growth; innovative development; financial stability